Can we modify maximal speed running posture? implications for performance and hamstring injury management - Mendiguchia, J.; Castaño-Zambudio, A.; Jiménez-Reyes, P.; Morin, J. B.; Edouard, P.; Conceição, F.; Tawiah-Dodoo, J.; Colyer, S. L. (International Journal of Sports Physiology and Performance, 2022)
Purpose: Sprint kinematics have been linked to hamstring injury and performance. This study aimed to examine if a specific 6-week multimodal intervention, combining lumbopelvic control and unning technique exercises, induced changes in pelvis and lower-limb kinematics at maximal speed and improved sprint performance.